وسطی و شمالی پنجاب کی دینی تعلیم کی روایت میں خانوادۂ بگویہ کا کردار(1826ء-1945ء):ایک تحقیقی مطالعہ: Role of Bugvī Family in Religious Education of Central and Northern Punjab (1826-1945AD): A Research Study - Amjad Muneer; Dr. Ghulam Shams-ur-Rehman (Al-Qamar, 2019)
This study aims to present the contribution of Famous Bugvī scholars of district Jhelum, later shifted to Bhera, in the tradition of religious education in central and northern Punjab during ninetieth and first half of twentieth century. It also provides an introduction to some of their disciples. It concludes that religious scholars of this family played a significant role in the dissemination of religious knowledge to the society in central and northern Punjab during the mentioned era. Their services as religious teachers are remarkable. They taught in the prominent institutions for religious studies like Madrasa Bāzār-e-Ḥakīmān Lahore, Madrasa Nīla Gumbad Lahore, Madrasa Noʻmānia Lahore, Madrasa Anjuman Ḥimāyat-e-Islam Lahore and Madrasa Jāmiʻ Masjid Bhera etc. They produced many renowned Islamic scholars of their time who have been playing a pivotal role in religious understandings of the region.